High resolution processed line aerogravity data over James Ross Island, Northern Antarctic Peninsula (1997/1998) - Jones, P.C.; Jordan, Tom; Ferraccioli, Fausto; Ghidella, Maria (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Airborne gravity data were collected using a Zero Length Spring Corporation (ZLS)-modified LaCoste and Romberg model S air-sea gravimeter. The meter was mounted in a gyro-stabilised, shock mounted platform at the centre of mass of the aircraft to minimise the effect of vibrations and rotational motions. GPS data were recorded with an Ashtech Z12 dual frequency receiver in the aircraft and at a fixed base station. Differential, carrier phase, kinematic GPS methods were then used to calculate all the navigational information used for the dynamic corrections of the aerogravity data. Standard processing steps were taken to convert the raw gravity data to free air anomalies, including latitude, free air and Eotvos corrections. The vertical accelerations of the aircraft, which dominate the gravity signal recorded by the meter, were calculated by double differencing GPS height measurements. In addition, a correction was made for gravimeter reading errors caused by the platform tilting when it was subjected to horizontal accelerations (Swain, 1996). After making the above corrections, the data were low pass filtered for wavelengths less than 9 km to remove short wavelength noise from the geological signal. The data were continued to a common altitude of 2050 m and levelled. Cross-over analysis at 118 intersections yielded a standard deviation of 2.9 mGal, which is within the 1-5 mGal error range typically reported for airborne gravity surveys after levelling. Comparison between airborne measurements and previous land-based gravity data (Garrett, 1990), yielded an RMS difference of ~4.5 mGal, which is within the 2 sigma range for airborne gravity data accuracy. : Airborne gravity data are presented in Jordan et al (2009) as are further details on survey design and data processing. The dataset available here includes channels from raw through to filtered and upward continued free air anomalies, where data was recoverable. All data is provided in a "by flight" database. Processing steps: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 38 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = (Spr_tens_real+((beam_vel)*k_fac)+CC)*scale_value, k_fac=30, meter scale value =0.9966. Still readings (Still) are in mGal and were calculating assuming a 2nd order best fit to the approximately linear drift of the meter observed at the tie down points. Airborne absolute gravity values (Abs_grav) = Rec_grav- Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984), with a 3 point mean filter applied after differencing to reduce short wavelength noise. Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Filtered free air anomaly (FAA_filt) used 9 km 1/2 wavelength space domain kernel filter (Holt et al., 2006). Final free air data (FAA) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Upward continued free air anomaly (FAAup) was produced by upward continuing free air data from the maximum flight altitude to 2050 m. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1:12 Lon Longitude WGS 1984, for processing see readme Lat Latitude WGS 1984, for processing see readme x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984, for processing see location data page Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction EotvosCor Eotvos correction LatCor Latitude correction FaCor Free air correction HaccCor Horizontal acceleration correction Free air Channels FAA Un-filtered free air anomaly FAA2050 Upward continued FAA data to a common flight altitude of 2050 m. *Projected coordinates (x and y) are in Polar sterographic defined as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin: 0.994 False easting 0 False northing 2082760.109 Positioning for the JRI survey used an Ashtech Z12 dual frequency receiver in the aircraft and at a fixed base station (Jordan et al., 2009). Differential, carrier phase, kinematic GPS methods were then used to calculate all the navigational information used. Positions are calculated for the phase centre of the aircraft antenna. All positions (Lat, lon and height) are referred to the WGS1984 ellipsoid. Database channels are described in the table below.